PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS X IPA SMA KRISTEN YABT MANOKWARI PADA MATERI LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Solince Morin (Universitas Papua, Manokwari, Indonesia, 2020)
Abstract This study aims to determine the effect of the STAD learning model on the cognitive learning outcomes of students on Electrolyte and Non-Electrolyte Solution material of class X IPA SMA Kristen YABT Manokwari. The research method used was pre-experimental design in the form of one group pretest-postest design. The retrieval technique uses saturated sampling. The data collection tool is a test of learning outcomes. Based on the result of the data processing obtained, the average pretest score was 48.22 and the postest average score was 96.00. Based on the result of the paired sample t-test, it was found that there were significant pretest and postest mean scores on the cognitive learning outcomes of students using the STAD type cooperative learning model which gave an effect of 20.15%. Key words: Learning model, STAD,Cognitive learning outcomes, and Electrolyte Solutions Non-Electrolyte